Capturing deliberative argument: An analytic coding scheme for studying argumentative dialogue and its benefits for learning. (October 2022) - Felton, Mark; Crowell, Amanda; Garcia-Mila, Merce; Villarroel, Constanza
Abstract: Deliberative argument refers to a collaborative argumentative exchange in which speakers hold incompatible views and seek to resolve these differences to arrive at a consensual decision. Studies have shown that some of the features of deliberative argument emerge under conditions where the goals of argument are structured to promote consensus-seeking, rather than competition. In a series of studies we have shown that deliberative argument is associated with greater learning and reasoning outcomes among adolescents and young adults when compared with persuasive argument. In this paper, we present the argumentative discourse coding scheme we have developed to identify the elements of deliberative argument based on normative models of argumentative discourse. We go on to demonstrate how the coding scheme can be used to unpack the potential educational benefits of deliberative argument over other types of argumentative discourse. In so doing, we hope to offer an empirical framework for understanding how best to leverage the power of argumentation in educational settings.